Galvanized Steel Sheet

By forming fine ferrite phases with controlled internal oxides, the plated steel sheet effectively prevents Zn penetration, enhancing LME resistance and maintaining structural integrity during high-temperature processing.

JP7617479B2Active Publication Date: 2025-01-20NIPPON STEEL CORPORATION
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2023551922
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-10-01
Filing Date
2022-09-30
Publication Date
2025-01-20
Estimated Expiration
2042-09-30

AI Technical Summary

Technical Problem

High-strength plated steel sheets used in applications like automobiles and building materials face issues with liquid metal embrittlement (LME) due to Zn penetration during high-temperature processing, leading to cracks and deteriorated fatigue properties.

Method used

The formation of fine ferrite phases with internal oxides near the steel sheet surface, controlled to specific densities and sizes, acts as trap sites for Zn, preventing its penetration and enhancing LME resistance.

Benefits of technology

The solution significantly reduces Zn penetration, thereby improving LME resistance and maintaining the steel's structural integrity during hot stamping and welding processes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007617479000003
    Figure 0007617479000003
  • Figure 0007617479000001
    Figure 0007617479000001
  • Figure 0007617479000002
    Figure 0007617479000002
Patent Text Reader

Abstract

The present invention provides a high-strength plated steel sheet excellent in LME resistance. This plated steel sheet has a Zn-containing plating layer on a steel sheet. The steel sheet has a tensile strength of 780 MPa or higher; the steel sheet has a chemical component composition comprising, by mass%, 0.05 to 0.40% of C, 0.2 to 3.0% of Si, 0.1 to 5.0% of Mn, 0.4 to 1.50% of sol. Al, etc., and the balance Fe and impurities; and in any vertical cross-section of the steel sheet, a region up to 2 µm deep from the surface contains ferrite phases having an equivalent circle diameter of 1 µm or less at a number density of 2 to 30 / µm2, and the ferrite phase contains internal oxides having an equivalent circle diameter of 2 to 100 nm at a number density of 3 / µm2 or higher.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a plated steel sheet. More specifically, the present invention relates to a plated steel sheet having high strength and excellent LME resistance. [Background technology]

[0002] In recent years, efforts have been made to increase the strength of steel sheets used in various fields such as automobiles, home appliances, and building materials. For example, in the automobile field, the use of high-strength steel sheets has been increasing in order to reduce the weight of vehicle bodies in order to improve fuel efficiency. Such high-strength steel sheets typically contain elements such as C, Si, Mn, and Al to improve the strength of the steel.

[0003] In the manufacture of high-strength steel sheets, heat treatment such as annealing is generally performed after rolling. Among the elements typically contained in high-strength steel sheets, Si, Mn, and Al, which are easily oxidized elements, may combine with oxygen in the atmosphere during the heat treatment to form a layer containing oxides near the surface of the steel sheet. Examples of the form of such a layer include a form in which an oxide containing Si, Mn, or Al is formed as a film on the outside (surface) of the steel sheet (external oxide layer), and a form in which an oxide is formed inside (surface layer) of the steel sheet (internal oxide layer).

[0004] When a plating layer (e.g., a Zn-based plating layer) is formed on the surface of a steel sheet with an outer oxide layer, the oxide exists as a film on the surface of the steel sheet, which inhibits interdiffusion between the steel components (e.g., Fe) and the plating components (e.g., Zn), affecting the adhesion between the steel and the plating, and resulting in insufficient plating (e.g., an increase in unplated areas). Therefore, from the viewpoint of improving plating, a steel sheet with an inner oxide layer is more preferable than a steel sheet with an outer oxide layer.

[0005] With regard to the internal oxidation layer, Patent Documents 1 and 2 describe a high-strength plated steel sheet having a tensile strength of 980 MPa or more, which is a plated steel sheet having a zinc-based plating layer on a base steel sheet containing C, Si, Mn, Al, etc., and which has an internal oxidation layer containing oxides of Si and / or Mn in the surface layer of the base steel sheet. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2016-130357 A [Patent Document 2] JP 2018-193614 A Summary of the Invention [Problem to be solved by the invention]

[0007] High-strength plated steel sheets are used in a variety of fields, including automotive components, home appliances, and building materials. When hot stamp forming or welding is performed on a plated steel sheet having a Zn-based plating layer on a high-strength steel sheet, the plated steel sheet is processed at high temperatures (e.g., about 900°C), and the Zn contained in the plating layer may be in a molten state during processing. In this case, the molten Zn may penetrate into the steel sheet and cause cracks inside the steel sheet. This phenomenon is called liquid metal embrittlement (LME), and it is known that the fatigue properties of the steel sheet are deteriorated due to the LME. Therefore, in order to prevent LME cracking, it is effective to suppress the penetration of Zn and other elements contained in the plating layer into the steel sheet.

[0008] Patent Documents 1 and 2 teach that by controlling the average depth of the internal oxide layer to be 4 μm or thicker and making the internal oxide layer function as a hydrogen trapping site, it is possible to prevent hydrogen penetration and suppress hydrogen embrittlement. However, no study is made on improving LME resistance.

[0009] In view of the above circumstances, an object of the present invention is to provide a high-strength plated steel sheet having excellent LME resistance. [Means for solving the problem]

[0010] The present inventors have found that, in order to solve the above problems, it is important to form oxides in the surface layer of a steel sheet, i.e., inside the steel sheet, and further to control the form of the oxides present in the surface layer of the steel sheet. More specifically, the present inventors have found that it is important to form fine (circle equivalent diameter 1 μm or less) ferrite phases at a predetermined number density (2 particles / μm) in the vicinity of the steel sheet surface (within a range of 2 μm deep from the surface). 2 or more), and the ferrite phase contains internal oxides (circular equivalent diameter 2 to 100 nm) at a predetermined number density (3 particles / μm 2 It has been found that by containing Zn in the above range, the internal oxides can function as trap sites for Zn that can penetrate into the steel during hot stamp forming or welding, thereby achieving high LME resistance.

[0011] The present invention has been made based on the above findings, and the gist of the present invention is as follows. (1) A plated steel sheet having a plating layer containing Zn on a steel sheet, the steel sheet having a tensile strength of 780 MPa or more and a chemical composition of the steel sheet in mass%, C: 0.05-0.40%, Si: 0.2-3.0%, Mn: 0.1-5.0%, sol.Al: 0.4-1.50%, P:0.0300% or less, S: 0.0300% or less, N: 0.0100% or less, B: 0~0.010%, Ti: 0 to 0.150%, Nb: 0 to 0.150%, V: 0~0.150%, Cr: 0-2.00%, Ni: 0-2.00%, Cu: 0-2.00%, Mo: 0-1.00%, W: 0 to 1.00%, Ca: 0 to 0.100%, Mg: 0~0.100%, Zr: 0 to 0.100%, Hf: 0 to 0.100%, and REM: 0 to 0.100%, with the balance being Fe and impurities; In any vertical cross section of the steel sheet, in a region from the surface to a depth of 2 μm, ferrite phases with a circle equivalent diameter of 1 μm or less are present at a number density of 2 to 30 particles / μm 2 The ferrite phase contains internal oxides with a circle equivalent diameter of 2 to 100 nm at a number density of 3 / μm 2 Galvanized steel sheet containing the above. (2) The shape of the inner oxide has an aspect ratio of 1.5 to 20, a minor axis of 1 to 20 nm, and a number density of 3 to 30 particles / μm 2 The plated steel sheet according to (1), (3) The plated steel sheet according to (1) or (2), wherein the inner oxide is at least one of Al and O, Al, Si and O, Al, Mn and O, and Al, Si, Mn and O, and the Al contained in the inner oxide is 20 to 53 mass %. (4) The plated steel sheet according to any one of (1) to (3), wherein the plating layer has a composition, in mass %, of Al: 0.3 to 1.5%, with the balance being Zn and impurities. (5) The plated steel sheet according to any one of (1) to (3), wherein the plating layer has a composition, in mass %, of Al: 0 to less than 0.1%, with the balance being Zn and impurities. Effect of the Invention

[0012] According to the present invention, the internal oxides of the fine ferrite phase present in the surface layer of the steel sheet function as trap sites for Zn that penetrates into the steel during hot stamp forming or welding, greatly suppressing the amount of Zn that penetrates, and greatly improving LME resistance. Therefore, the present invention makes it possible to obtain excellent LME resistance in a high-strength steel sheet. [Brief description of the drawings]

[0013] [Figure 1] 1 shows a photograph of a cross section of an exemplary steel plate according to the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] <Plated steel sheets> The plated steel sheet according to the present invention is a plated steel sheet having a Zn-containing plating layer on a steel sheet, The tensile strength of the steel plate is 780 MPa or more, The chemical composition of the steel sheet is expressed as mass%: C: 0.05-0.40%, Si: 0.2-3.0%, Mn: 0.1-5.0%, sol.Al: 0.4-1.50%, P:0.0300% or less, S: 0.0300% or less, N: 0.0100% or less, B: 0~0.010%, Ti: 0 to 0.150%, Nb: 0 to 0.150%, V: 0~0.150%, Cr: 0-2.00%, Ni: 0-2.00%, Cu: 0-2.00%, Mo: 0-1.00%, W: 0 to 1.00%, Ca: 0 to 0.100%, Mg: 0~0.100%, Zr: 0 to 0.100%, Hf: 0 to 0.100%, and REM: 0 to 0.100%, with the balance being Fe and impurities. In any vertical cross section of the steel sheet, ferrite phases with a circle equivalent diameter of 1 μm or less are present in a region from the surface layer to a depth of 2 μm at a number density of 2 to 30 particles / μm. 2 The ferrite phase contains internal oxides with a circle equivalent diameter of 2 to 100 nm at a number density of 3 / μm 2 The present invention is characterized in that it contains the above.

[0015] In the manufacture of high-strength steel sheets, a steel slab adjusted to a predetermined composition is rolled (typically hot rolling and cold rolling), and then annealed in order to obtain a desired structure, etc. In this annealing process, components in the steel sheet that are relatively easily oxidized (e.g., Si, Mn, Al) combine with oxygen in the annealing atmosphere to form a layer containing oxides near the surface of the steel sheet.

[0016] In this regard, the photograph in Figure 1 is an example of a cross section of a plated steel sheet according to this embodiment. The photograph on the left in Figure 1 shows the cross-sectional structure of the plated steel sheet in the range of 2 μm deep from the steel sheet surface (interface between the plated layer and the steel sheet) toward the steel sheet side. Ferrite phases constituting the structure, which have an equivalent circle diameter of 1 μm or less, can also be confirmed. The photograph on the right in Figure 1 is an enlarged view of a portion of the photograph on the left. It can be confirmed that rod-shaped internal oxides (indicated by arrows) with an equivalent circle diameter of 100 nm or less are present inside the ferrite phase.

[0017] When hot stamp forming or welding is performed on a plated steel sheet having a Zn-containing plating layer provided on the surface of the steel sheet, the temperature becomes high during processing, and the Zn contained in the plating layer may melt. When Zn melts, the molten Zn penetrates into the steel, and when processing is performed in this state, liquid metal embrittlement (LME) cracks occur inside the steel sheet, and the fatigue properties of the steel sheet may deteriorate due to the LME. The present inventors have discovered that, as described above, when a fine ferrite phase and its internal oxide have a desired number density near the surface layer of a steel sheet, it contributes to improving LME resistance. More specifically, it has been found that the internal oxide of the fine ferrite phase functions as a trap site for Zn that attempts to penetrate into the steel during processing at high temperatures. As a result, for example, Zn that attempts to penetrate into the steel during hot stamp forming is captured by the internal oxide of the fine ferrite phase on the surface layer of the steel sheet, and the penetration of Zn into the inside of the steel sheet is suitably suppressed. Therefore, it has been found that in order to improve LME resistance, it is important to have the internal oxide of the fine ferrite phase present at a predetermined number density.

[0018] More specifically, when Zn contained in the plating layer is melted by hot stamp forming or welding, the molten Zn diffuses from the interface of the steel sheet on which the plating layer is provided (the interface between the plating layer and the steel sheet) in the depth direction of the steel sheet. At this time, the molten Zn diffuses along the grain boundaries of the crystal grains constituting the steel sheet structure, and also diffuses from the grain boundaries into the crystal grains. If an internal oxide exists in the crystal grain, the Zn is trapped by the internal oxide, and the Zn is suppressed from further diffusing into the steel sheet. In this embodiment, since the ferrite phase near the steel sheet surface is fine (compared to when the ferrite phase is coarse), there are many paths of the grain boundary (or phase interface), and the distance from the grain boundary to the internal oxide in the grain (or phase) is short, so that the trapping of the molten Zn by the internal oxide of the ferrite phase proceeds quickly. That is, the molten Zn is quickly trapped near the surface of the steel sheet, and the diffusion into the steel sheet, particularly to a location deeper than the steel sheet surface, is significantly suppressed. As a result, liquid metal embrittlement (LME) cracking inside the steel plate is suppressed, and the deterioration of the fatigue properties of the steel plate due to the LME is also suppressed. Note that, since the metal structure of the surface layer of the steel plate is typically composed of a metal structure that is softer than that of the inside of the steel plate (e.g., at the 1 / 8 or 1 / 4 position of the plate thickness), liquid metal embrittlement (LME) cracking does not pose a particular problem even if Zn is present in the surface layer of the steel plate.

[0019] The steel plate according to the present invention will be described in detail below. The thickness of the steel plate according to the present invention is not particularly limited, but may be, for example, 0.1 to 3.2 mm.

[0020] [Steel plate composition] The composition of the steel sheet according to the present invention will be described. Unless otherwise specified, "%" regarding the content of an element means "mass%". In the numerical range of the composition, a numerical range expressed with "~" means a range including the numerical values ​​written before and after "~" as the lower and upper limits, unless otherwise specified.

[0021] (C: 0.05~0.40%) C (carbon) is an important element for ensuring the strength of steel. If the C content is insufficient, sufficient strength may not be ensured. Furthermore, if the C content is insufficient, the desired internal oxide morphology may not be obtained. Therefore, the C content is 0.05% or more, preferably 0.07% or more, more preferably 0.10% or more, and even more preferably 0.12% or more. On the other hand, if the C content is excessive, the weldability may decrease. Therefore, the C content is 0.40% or less, preferably 0.35% or less, and more preferably 0.30% or less.

[0022] (Si: 0.2 to 3.0%) Si (silicon) is an element effective in improving the strength of steel. If the Si content is insufficient, sufficient strength may not be ensured. Furthermore, Si forms oxides together with Mn, functions as pinning particles, and contributes to the refinement of the ferrite phase. In other words, if the Si content is insufficient, the desired fine ferrite phase and its internal oxide may not be sufficiently generated near the surface layer of the steel sheet. Therefore, the Si content is 0.2% or more, preferably 0.3% or more, more preferably 0.5% or more, and even more preferably 1.0% or more. On the other hand, if the Si content is excessive, it may cause deterioration of the surface properties and may also promote the growth of external oxidation. Therefore, the Si content is 3.0% or less, preferably 2.5% or less, and more preferably 2.0% or less.

[0023] (Mn: 0.1-5.0%) Mn (manganese) is an element that is effective in improving the strength of steel by obtaining a hard structure. If the Mn content is insufficient, sufficient strength may not be ensured. Furthermore, Mn forms oxides with Si, functions as pinning particles, and contributes to the refinement of the ferrite phase. In other words, if Mn is insufficient, the desired fine ferrite phase and its internal oxide may not be sufficiently generated near the surface layer of the steel sheet. Therefore, the Mn content is 0.1% or more, preferably 0.5% or more, more preferably 1.0% or more, and even more preferably 1.5% or more. On the other hand, if the Mn content is excessive, the metal structure may become non-uniform due to Mn segregation, which may reduce workability and may promote external oxidation growth. Therefore, the Mn content is 5.0% or less, preferably 4.5% or less, more preferably 4.0% or less, and even more preferably 3.5% or less.

[0024] (sol.Al:0.4~1.50%) Al (aluminum) is an element that acts as a deoxidizing element. If the Al content is insufficient, there is a risk that the effect of deoxidization cannot be sufficiently secured. Furthermore, there is a risk that the desired oxide, particularly the internal oxide of the fine ferrite phase, is not sufficiently generated near the surface layer of the steel sheet. Al is contained in the internal oxide together with Si and Mn, and functions as a pinning particle, contributing to the refinement of the ferrite phase. The Al content may be 0.4% or more, but in order to obtain a sufficient desired effect, the internal oxide of the fine ferrite phase, the Al content is 0.5% or more, preferably 0.6% or more, and more preferably 0.7% or more. On the other hand, if the Al content is excessive, there is a risk that the workability is reduced and the surface properties are deteriorated, and there is a risk that the growth of external oxide is promoted. Therefore, the Al content is 1.50% or less, preferably 1.20% or less, and more preferably 0.80% or less. The Al content means the content of so-called acid-soluble Al (sol.Al).

[0025] (P:0.0300% or less) P (phosphorus) is an impurity generally contained in steel. If the P content exceeds 0.0300%, the weldability may be reduced. Therefore, the P content is 0.0300% or less, preferably 0.0200% or less, more preferably 0.0100% or less, and further preferably 0.0050% or less. The lower limit of the P content is not particularly limited, but from the viewpoint of manufacturing costs, the P content may be more than 0% or 0.0001% or more.

[0026] (S:0.0300% or less) S (sulfur) is an impurity generally contained in steel. If the S content exceeds 0.0300%, the weldability is reduced, and furthermore, the amount of MnS precipitated increases, which may reduce workability such as bendability. Therefore, the S content is 0.0300% or less, preferably 0.0100% or less, more preferably 0.0050% or less, and further preferably 0.0020% or less. The lower limit of the S content is not particularly limited, but from the viewpoint of desulfurization costs, the S content may be more than 0% or 0.0001% or more.

[0027] (N:0.0100% or less) N (nitrogen) is an impurity generally contained in steel. If the N content exceeds 0.0100%, the weldability may be reduced. Therefore, the N content is 0.0100% or less, preferably 0.0080% or less, more preferably 0.0050% or less, and further preferably 0.0030% or less. There is no particular lower limit for the N content, but from the viewpoint of manufacturing costs, the N content may be more than 0% or 0.0010% or more.

[0028] (B: 0~0.010%) Since B (boron) is an element that improves hardenability and contributes to improving strength, and also segregates at grain boundaries to strengthen the grain boundaries and improve toughness, it may be contained as necessary. Therefore, the B content is 0% or more, preferably 0.001% or more, more preferably 0.002% or more, and even more preferably 0.003% or more. On the other hand, from the viewpoint of ensuring sufficient toughness and weldability, the B content is 0.010% or less, preferably 0.008% or less, and more preferably 0.006% or less.

[0029] (Ti: 0 to 0.150%) Ti (titanium) is an element that precipitates as TiC during cooling of steel and contributes to improving strength, so it may be contained as necessary. Therefore, the Ti content is 0% or more, preferably 0.001% or more, more preferably 0.003% or more, even more preferably 0.005% or more, and even more preferably 0.010% or more. On the other hand, if it is contained excessively, coarse TiN may be generated and toughness may be impaired, so the Ti content is 0.150% or less, preferably 0.100% or less, and more preferably 0.050% or less.

[0030] (Nb: 0~0.150%) Since Nb (niobium) is an element that contributes to improving strength through improving hardenability, it may be contained as necessary. Therefore, the Nb content is 0% or more, preferably 0.010% or more, more preferably 0.020% or more, and even more preferably 0.030% or more. On the other hand, from the viewpoint of ensuring sufficient toughness and weldability, the Nb content is 0.150% or less, preferably 0.100% or less, and more preferably 0.060% or less.

[0031] (V:0~0.150%) V (vanadium) is an element that contributes to improving strength through improving hardenability, so it may be contained as necessary. Therefore, the V content is 0% or more, preferably 0.010% or more, more preferably 0.020% or more, and even more preferably 0.030% or more. On the other hand, from the viewpoint of ensuring sufficient toughness and weldability, the V content is 0.150% or less, preferably 0.100% or less, and more preferably 0.060% or less.

[0032] (Cr:0~2.00%) Cr (chromium) is effective in increasing the hardenability of steel and increasing its strength, so it may be contained as necessary. Therefore, the Cr content is 0% or more, preferably 0.10% or more, more preferably 0.20% or more, even more preferably 0.50% or more, and even more preferably 0.80% or more. On the other hand, if it is contained in excess, a large amount of Cr carbide is formed, which may adversely impair the hardenability, so the Cr content is 2.00% or less, preferably 1.80% or less, and more preferably 1.50% or less.

[0033] (Ni: 0-2.00%) Ni (nickel) is effective in increasing the hardenability of steel and increasing the strength of steel, so it may be contained as necessary. Therefore, the Ni content is 0% or more, preferably 0.10% or more, more preferably 0.20% or more, even more preferably 0.50% or more, and even more preferably 0.80% or more. On the other hand, since excessive addition of Ni leads to an increase in cost, the Ni content is 2.00% or less, preferably 1.80% or less, and more preferably 1.50% or less.

[0034] (Cu: 0-2.00%) Cu (copper) is effective in increasing the hardenability of steel and increasing the strength of steel, so it may be contained as necessary. Therefore, the Cu content is 0% or more, preferably 0.10% or more, more preferably 0.20% or more, even more preferably 0.50% or more, and even more preferably 0.80% or more. On the other hand, from the viewpoint of suppressing a decrease in toughness, cracking of the slab after casting, and a decrease in weldability, the Cu content is 2.00% or less, preferably 1.80% or less, and more preferably 1.50% or less.

[0035] (Mo:0~1.00%) Mo (molybdenum) is effective in increasing the hardenability of steel and increasing the strength of steel, so it may be contained as necessary. Therefore, the Mo content is 0% or more, preferably 0.10% or more, more preferably 0.20% or more, and even more preferably 0.30% or more. On the other hand, from the viewpoint of suppressing the deterioration of toughness and weldability, the Mo content is 1.00% or less, preferably 0.90% or less, and more preferably 0.80% or less.

[0036] (W:0~1.00%) W (tungsten) is effective in increasing the hardenability of steel and increasing the strength of steel, so it may be contained as necessary. Therefore, the W content is 0% or more, preferably 0.10% or more, more preferably 0.20% or more, and even more preferably 0.30% or more. On the other hand, from the viewpoint of suppressing the deterioration of toughness and weldability, the W content is 1.00% or less, preferably 0.90% or less, and more preferably 0.80% or less.

[0037] (Ca: 0~0.100%) Ca (calcium) is an element that contributes to inclusion control, particularly to finely dispersing inclusions, and has the effect of increasing toughness, so it may be contained as necessary. Therefore, the Ca content is 0% or more, preferably 0.001% or more, more preferably 0.005% or more, even more preferably 0.010% or more, and even more preferably 0.020% or more. On the other hand, if it is contained excessively, deterioration of surface properties may become apparent, so the Ca content is 0.100% or less, preferably 0.080% or less, and more preferably 0.050% or less.

[0038] (Mg: 0~0.100%) Mg (magnesium) is an element that contributes to inclusion control, particularly to finely dispersing inclusions, and has the effect of increasing toughness, so it may be contained as necessary. Therefore, the Mg content is 0% or more, preferably 0.001% or more, more preferably 0.003% or more, and even more preferably 0.010% or more. On the other hand, if it is contained excessively, deterioration of surface properties may become apparent, so the Mg content is 0.100% or less, preferably 0.090% or less, and more preferably 0.080% or less.

[0039] (Zr: 0~0.100%) Zr (zirconium) is an element that contributes to inclusion control, particularly to finely dispersing inclusions, and has the effect of increasing toughness, so it may be contained as necessary. Therefore, the Zr content is 0% or more, preferably 0.001% or more, more preferably 0.005% or more, and even more preferably 0.010% or more. On the other hand, if it is contained excessively, deterioration of surface properties may become apparent, so the Zr content is 0.100% or less, preferably 0.050% or less, and more preferably 0.030% or less.

[0040] (Hf:0~0.100%) Hf (hafnium) is an element that contributes to inclusion control, particularly to finely dispersing inclusions, and has the effect of increasing toughness, so it may be contained as necessary. Therefore, the Hf content is 0% or more, preferably 0.001% or more, more preferably 0.005% or more, and even more preferably 0.010% or more. On the other hand, if it is contained excessively, deterioration of surface properties may become apparent, so the Hf content is 0.100% or less, preferably 0.050% or less, and more preferably 0.030% or less.

[0041] (REM:0~0.100%) REM (rare earth elements) are elements that contribute to inclusion control, particularly to finely dispersing inclusions, and have the effect of increasing toughness, and may be contained as necessary. Therefore, the REM content is 0% or more, preferably 0.001% or more, more preferably 0.005% or more, and even more preferably 0.010% or more. On the other hand, if contained excessively, deterioration of surface properties may become apparent, so the REM content is 0.100% or less, preferably 0.050% or less, and more preferably 0.030% or less. REM is an abbreviation for Rare Earth Metal, and refers to elements belonging to the lanthanoid series. REM is usually added as misch metal.

[0042] The balance of the steel sheet according to the present invention other than the above-mentioned composition is composed of Fe and impurities. Here, the impurities refer to components that are mixed in due to various factors in the manufacturing process, including raw materials such as ores and scraps, during industrial production of the steel sheet, and are allowed to be contained within a range that does not adversely affect the properties of the steel sheet according to the present invention.

[0043] In the present invention, the composition of the steel sheet may be analyzed by an elemental analysis method known to those skilled in the art, for example, inductively coupled plasma mass spectrometry (ICP-MS). However, C and S may be measured by a combustion-infrared absorption method, and N may be measured by an inert gas fusion-thermal conductivity method. These analyses may be performed on samples taken from the steel sheet by a method conforming to JIS G0417:1999.

[0044] The amount of sol. Al can be measured by the following procedure. Specifically, the steel sheet is electrolyzed, and the residue collected by filter paper is analyzed by inductively coupled plasma mass spectrometry. The detected amount of Al is the amount of precipitated Al. Meanwhile, the steel sheet is not electrolyzed, and T. Al (also called "total Al") is measured. The value obtained by subtracting the amount of precipitated Al from T. Al is defined as sol. Al.

[0045] [surface] In the present invention, the "surface layer" of a steel sheet means a region from the surface of the steel sheet (the interface between the steel sheet and the plating layer in the case of a plated steel sheet) to a predetermined depth in the sheet thickness direction, and the "predetermined depth" is typically 50 μm or less. Note that the shape and number density of the fine ferrite phase and its internal oxides according to this embodiment are measured in the "surface layer" within a range of 2 μm deep from the steel sheet surface (the interface between the plating layer and the steel sheet) toward the steel sheet side. This range is sometimes referred to as the "surface vicinity."

[0046] As illustrated in FIG. 1, in the plated steel sheet according to this embodiment, a fine ferrite phase and its internal oxides are present in the surface layer of the steel sheet.

[0047] [Ferrite phase] In this embodiment, the term "ferrite phase" refers to a crystal phase constituting the matrix of steel and having a ferrite crystal structure. In reality, the ferrite phase is typically present three-dimensionally in a spherical or nearly spherical shape in the surface layer of the steel sheet, and therefore, when a cross section of the surface layer of the steel sheet is observed, the ferrite phase is typically observed in a circular or nearly circular shape.

[0048] (Circle equivalent diameter of ferrite phase) In this embodiment, the ferrite phase has a circle equivalent diameter of 1 μm (1000 nm) or less, and the ferrite phase in this range may be referred to as a fine ferrite phase. By controlling the circle equivalent diameter to such a range, the fine ferrite phase can be dispersed near the surface layer of the steel sheet, and the internal oxide of the fine ferrite phase functions well as a trap site for Zn that may enter when the plated steel sheet having a plating layer formed on the steel sheet is subjected to hot stamp forming or welding processing. On the other hand, if the circle equivalent diameter exceeds 1 μm (1000 nm), the number of ferrite phases may decrease, and the desired number density may not be obtained. The circle equivalent diameter of the ferrite phase is not particularly limited to a lower limit, but may be 2 nm or more, preferably 10 nm or more, so as to include the internal oxide described later.

[0049] (number density of ferrite phase) In this embodiment, the number density of fine ferrite phases in the vicinity of the surface layer (the region from the surface layer to a depth of 2 μm) is 2 to 30 particles / μm 2 By controlling the number density within this range, a large amount of fine ferrite phases can be dispersed in the surface layer of the steel sheet, and the internal oxides can be contained within the fine ferrite phases. The internal oxides function well as trap sites for Zn that can penetrate when the plated steel sheet having a plating layer formed on the steel sheet is subjected to hot stamp forming or welding. Since the circle equivalent diameter of the ferrite phase is fine (circle equivalent diameter 1 μm or less) (compared to coarse ferrite phases), Zn that penetrates the ferrite phase quickly reaches the internal oxides, and the Zn is quickly trapped. Conversely, if the ferrite phase is coarse, it takes time for the Zn that penetrates the ferrite phase to reach the internal oxides, and the Zn may not be trapped. Therefore, when the number density of the fine ferrite phase is 2 particles / μm 2 If the density is less than 100%, the number of relatively coarse ferrite phases increases, and most of the internal oxides acting as Zn trap sites are present in the coarse ferrite phases, which do not function adequately as Zn trap sites, and there is a risk that good LME resistance cannot be obtained. 2 More preferably, 4 / μm 2 More preferably, 5 / μm 2 The fine ferrite phase is preferably present in a large amount from the viewpoint of containing the internal oxides that function as Zn trap sites. However, under general manufacturing conditions, the upper limit of the number density of the fine ferrite phase is 30 pieces / μm 2 Therefore, the upper limit of the number density of the fine ferrite phase in this embodiment is 30 particles / μm 2 Less than 25 particles / μm 2 Below, 20 pieces / μm 2 It may be the following.

[0050] The size (circle equivalent diameter) and number density of the ferrite phase are measured by a scanning electron microscope (SEM) and a transmission electron microscope (TEM). Specific measurements are as follows. A cross section of the surface layer of the steel sheet is observed by SEM to obtain an SEM image including the ferrite phase. A test piece for TEM observation is taken from the cross-sectional SEM image by FIB processing so as to include the interface between the plating layer and the steel sheet. In the TEM observation, a ferrite phase (circle equivalent diameter of 1 μm or less) corresponding to the shape shown in this embodiment is identified within a range of 2 μm deep from the steel sheet surface (interface between the plating layer and the steel sheet) to the steel sheet side, and its number density is measured. The observation position is 2.0 μm from the steel sheet surface in the depth direction (direction perpendicular to the steel sheet surface) and 1.0 μm from any position in the TEM image in the width direction (direction parallel to the steel sheet surface). In other words, the observation field area is 2.0 μm × 1.0 μm. Next, the TEM image of each region obtained as described above is extracted and binarized to separate each ferrite phase (and grain boundary (or phase interface)). The area of ​​each ferrite phase is calculated from each binarized image. The area of ​​each ferrite phase is calculated as the diameter of a circle having an area equal to the calculated area, i.e., the equivalent circle diameter (nm) of the ferrite phase is calculated as the equivalent circle diameter. Ferrite phases having an equivalent circle diameter of 1 μm or less (1000 nm or less) are defined as fine ferrite phases according to this embodiment. Furthermore, the number of fine ferrite phases in each binarized image is counted. The average number of fine ferrite phases in the total of the 10 regions thus calculated is taken as the number density of fine ferrite phases (pieces / μm 2 Note that when only a part of the ferrite phase is observed in the observation area, that is, when the entire outline of the ferrite phase is not within the observation area, it is not counted.

[0051] [Inner oxide] In this embodiment, the term "internal oxide" refers to an oxide present inside the fine "ferrite phase" described above. A single ferrite phase may have a plurality of internal oxides, and the positions of the internal oxides may not be arranged according to a specific rule (for example, linearly) but may be arranged randomly.

[0052] (Internal oxide particle size) In this embodiment, the particle diameter of the internal oxide is 2 nm or more and 100 nm or less in circle equivalent diameter. By controlling the particle diameter within such a range, the internal oxide can be dispersed in the fine ferrite phase present in the vicinity of the surface layer of the steel sheet, and the internal oxide functions well as a trap site for Zn that may enter when the plated steel sheet having a plating layer formed on the steel sheet is subjected to hot stamp forming or welding processing. On the other hand, if the particle diameter exceeds 100 nm, the number of internal oxides may decrease, and the desired number density may not be obtained. The finer the internal oxide is, the higher the specific surface area becomes, and the more reactive it is as a trap site, so the particle diameter of the internal oxide may be 50 nm or less, preferably 20 nm or less or less than 20 nm. On the other hand, the lower limit is 2 nm or more. The reason is that the amount of Zn that can be trapped per particle decreases, and Zn cannot be sufficiently trapped, and the internal oxide may not function sufficiently as a trap site for Zn. The shape of the inner oxide is not particularly limited, but the aspect ratio (maximum line segment length crossing the inner oxide (major axis) / maximum line segment length crossing the oxide perpendicular to the major axis (minor axis)) may be 1.5 or more, and the minor axis may be less than 20 nm. Without wishing to be bound by a particular theory, it is believed that when the aspect ratio of the inner oxide is high, the possibility of contacting Zn that has infiltrated into the ferrite phase increases, thereby increasing the Zn trapping efficiency.

[0053] (number density of inner oxide) The number density of the internal oxide is 3 / μm 2 That is all. By controlling the number density within this range, a large amount of internal oxides can be contained in the fine ferrite phase present in the surface layer of the steel sheet, and the internal oxides function well as trap sites for Zn that can enter when the plated steel sheet having a plating layer formed on the steel sheet is subjected to hot stamp forming or welding. On the other hand, when the number density is 3 particles / μm 2 If the number density of the inner oxides is less than 6 / μm, the number density of the inner oxides as Zn trap sites is insufficient, and the inner oxides do not function sufficiently as Zn trap sites, so that good LME resistance may not be obtained. 2More preferably, 8 particles / μm 2 More preferably, 10 particles / μm 2 The inner oxide is preferably present in a large amount from the viewpoint of functioning as a trap site for Zn, but since the circle equivalent diameter of the ferrite phase including the inner oxide is 1 μm or less, the number density of the inner oxide may be set at an upper limit of 30 particles / μm. 2 Below, 25 pieces / μm 2 Below, 20 pieces / μm 2 It may be the following.

[0054] The particle size and number density of the internal oxides are measured by a scanning electron microscope (SEM) and a transmission electron microscope (TEM) in the same manner as for the ferrite phase. The specific measurement is as follows. The cross section of the surface layer of the steel sheet is observed by SEM to obtain an SEM image including the internal oxides. A test piece for TEM observation is taken from the cross-sectional SEM image by FIB processing so as to include the interface between the plating layer and the steel sheet. In the TEM observation, the internal oxides (particle size 2 to 100 nm) corresponding to the shape shown in this embodiment are identified within a range of 2 μm deep from the steel sheet surface (interface between the plating layer and the steel sheet) to the steel sheet side, and their number density is measured. The observation position is 2.0 μm from the steel sheet surface in the depth direction (direction perpendicular to the steel sheet surface) and 1.0 μm from any position in the TEM image in the width direction (direction parallel to the steel sheet surface). In other words, the observation field area is 2.0 μm × 1.0 μm. Next, the TEM image of each region obtained as described above is extracted and binarized to separate the oxide portion from the steel portion. The area of ​​the internal oxide portion is calculated from each binarized image, and the particle size (nm) of the internal oxide is calculated as the diameter of a circle having the same area as the calculated area, i.e., the circle equivalent diameter. The particle size in the range of 2 nm to 100 nm is defined as the internal oxide according to this embodiment. Furthermore, the number of internal oxides in each binarized image is counted. The average value of the total number of internal oxides in the 10 regions thus calculated is taken as the number density of the internal oxides (pieces / μm 2 In addition, when only a part of the internal oxide is observed in the observation area, that is, when the entire outline of the internal oxide is not within the observation area, it is not counted.

[0055] [Oxide composition] In the present invention, the inner oxide (hereinafter, simply referred to as oxide) contains, in addition to oxygen, one or more of the elements contained in the steel sheet described above, and typically contains Si, O, and Fe, and may further contain Mn and Al. The oxide may contain elements (e.g., Cr, etc.) that may be contained in the steel sheet described above in addition to these elements. Although not wishing to be bound by a specific theory, it is believed that when the oxide contains Al, the effect as a trap site for Zn is enhanced, and therefore the content of Al contained in the inner oxide is preferably high, and may be 20 mass% or more. When the inner oxide is an oxide of Al and O, so-called alumina, the Al content in the oxide is the highest, at 53 mass%, and this may be set as the upper limit of the Al content.

[0056] <Plated steel sheets> The plated steel sheet according to the present invention has a plating layer containing Zn on the above-mentioned steel sheet according to the present invention. This plating layer may be formed on one side or both sides of the steel sheet. Examples of the plating layer containing Zn include a hot-dip galvanized layer, a galvannealed hot-dip galvanized layer, an electric galvanized layer, and an electric alloy galvanized layer. More specifically, examples of the plating type that can be used include Zn-0.2%Al (GI), Zn-(0.3 to 1.5)%Al, Zn-4.5%Al, Zn-0.09%Al-10%Fe (GA), Zn-1.5%Al-1.5%Mg, Zn-11%Al-3%Mg-0.2%Si, Zn-11%Ni, and Zn-15%Mg.

[0057] [Composition of plating layer] The composition of the components contained in the Zn-containing plating layer of the present invention will be described. Unless otherwise specified, "%" regarding the content of an element means "mass%". In the numerical range of the composition of the plating layer, the numerical range expressed by "~" means a range including the numerical values ​​written before and after "~" as the lower and upper limits, unless otherwise specified.

[0058] (Al: 0-60.0%) Since Al is an element that improves the corrosion resistance of the coating layer by being contained together with Zn or alloyed with Zn, it may be contained as necessary. Therefore, the Al content may be 0%. In order to form a coating layer containing Zn and Al, the Al content is preferably 0.01% or more, and may be, for example, 0.1% or more, 0.3% or more, 0.5% or more, 1.0% or more, or 3.0% or more. On the other hand, since the effect of improving the corrosion resistance is saturated when it exceeds 60.0%, the Al content is preferably 60.0% or less, and may be, for example, 55.0% or less, 50.0% or less, 40.0% or less, 30.0% or less, 20.0% or less, 10.0% or less, or 5.0% or less. Although the detailed mechanism is unknown, when the Al in the coating layer is in the range of 0.3 to 1.5%, the penetration speed of Zn into the steel grain boundary is significantly reduced due to the effect of Al, and it is possible to improve the LME resistance. Therefore, from the viewpoint of improving LME resistance, the Al content in the plating layer is preferably 0.3 to 1.5%. On the other hand, since the coating weight of electroplating is easily controlled by the amount of electricity, the Al content in the plating layer may be 0 to less than 0.1%. When the Al content in the plating layer is less than 0 to 0.1%, the alloying speed of the plating layer and the base steel is fast, and the Zn in the plating layer diffuses not only to the steel grain boundaries but also into the grains early during welding. As a result, intensive Zn penetration into the steel grain boundaries is suppressed, and it is possible to improve LME resistance. Typically, the plating layer may have a composition containing, by mass%, Al: 0.3 to 1.5%, with the balance being Zn and impurities, or the plating layer may have a composition containing, by mass%, Al: 0 to less than 0.1%, with the balance being Zn and impurities. The plating layer having a composition in this range can further improve LME resistance.

[0059] (Mg: 0-15.0%) Mg is an element that improves the corrosion resistance of the plating layer by being contained together with Zn and Al or alloyed with them, so it may be contained as necessary. Therefore, the Mg content may be 0%. In order to form a plating layer containing Zn, Al, and Mg, the Mg content is preferably 0.01% or more, and may be, for example, 0.1% or more, 0.5% or more, 1.0% or more, or 3.0% or more. On the other hand, if it exceeds 15.0%, Mg does not completely dissolve in the plating bath and floats as an oxide, and when zinc plating is performed with this plating bath, the oxide adheres to the plating surface layer, causing poor appearance, or there is a risk of non-plated parts occurring, so the Mg content is preferably 15.0% or less, and may be, for example, 10.0% or less, 5.0% or less.

[0060] (Fe: 0-15.0%) When a Zn-containing plating layer is formed on a steel sheet and then the plated steel sheet is heat-treated, Fe can be diffused from the steel sheet and contained in the plating layer. Therefore, in a state where no heat treatment is performed, Fe is not contained in the plating layer, and the Fe content may be 0%. The Fe content may be 1.0% or more, 2.0% or more, 3.0% or more, 4.0% or more, or 5.0% or more. On the other hand, the Fe content may be 15.0% or less, and may be, for example, 12.0% or less, 10.0% or less, 8.0% or less, or 6.0% or less.

[0061] (Si: 0-3.0%) Since Si is an element that further improves corrosion resistance when contained in a Zn-containing plating layer, particularly a Zn-Al-Mg plating layer, it may be contained as necessary. Therefore, the Si content may be 0%. From the viewpoint of improving corrosion resistance, the Si content may be, for example, 0.005% or more, 0.01% or more, 0.05% or more, 0.1% or more, or 0.5% or more. In addition, the Si content may be 3.0% or less, 2.5% or less, 2.0% or less, 1.5% or less, or 1.2% or less.

[0062] The basic composition of the plating layer is as described above. Furthermore, the plating layer may optionally contain one or more of Sb: 0-0.50%, Pb: 0-0.50%, Cu: 0-1.00%, Sn: 0-1.00%, Ti: 0-1.00%, Sr: 0-0.50%, Cr: 0-1.00%, Ni: 0-1.00%, and Mn: 0-1.00%. Although not particularly limited, from the viewpoint of fully exerting the action and function of the above basic components constituting the plating layer, the total content of these optional added elements is preferably 5.00% or less, more preferably 2.00% or less.

[0063] The remainder of the plating layer other than the above components is composed of Zn and impurities. The impurities in the plating layer refer to components that are mixed in due to various factors in the manufacturing process, including raw materials, when the plating layer is manufactured, and are not components that are intentionally added to the plating layer. The plating layer may contain trace amounts of elements other than the basic components and optional added components described above as impurities within a range that does not impair the effects of the present invention.

[0064] The component composition of the plating layer can be determined by dissolving the plating layer in an acid solution containing an inhibitor that suppresses corrosion of the steel sheet, and measuring the resulting solution by ICP (inductively coupled plasma) emission spectroscopy.

[0065] The thickness of the plating layer may be, for example, 3 to 50 μm. The coating weight of the plating layer is not particularly limited, but is, for example, 10 to 170 g / m per side. 2 In the present invention, the coating weight of the plating layer is determined by dissolving the plating layer in an acid solution to which an inhibitor that suppresses corrosion of the base steel has been added, and measuring the change in weight before and after dissolution of the plating layer.

[0066] [Tensile strength] The steel sheet and plated steel sheet according to the present invention preferably have high strength, specifically, a tensile strength of 780 MPa or more. For example, the tensile strength may be 780 MPa or more, 800 MPa or more, or 900 MPa or more. The upper limit of the tensile strength is not particularly limited, but may be, for example, 2000 MPa or less from the viewpoint of ensuring toughness. The tensile strength may be measured by taking a JIS No. 5 tensile test piece and measuring it in accordance with JIS Z 2241 (2011). The longitudinal direction of the tensile test piece is not particularly limited, and may be perpendicular to the rolling direction.

[0067] The plated steel sheet according to the present invention has high strength and high LME resistance, and therefore can be suitably used in a wide range of fields such as automobiles, home appliances, and building materials, but is particularly preferably used in the automobile field. Steel sheets and plated steel sheets used for automobiles are often hot stamped, in which case LME cracking can be a significant problem. Therefore, when the plated steel sheet according to the present invention is used as an automobile steel sheet, the effect of the present invention of having high LME resistance is suitably exhibited.

[0068] <Steel sheet manufacturing method> A preferred method for producing the steel plate according to the present invention will be described below. The following description is intended to exemplify a characteristic method for producing the steel plate according to the present invention, and is not intended to limit the steel plate to one produced by the production method described below.

[0069] The steel sheet according to the present invention can be obtained by, for example, carrying out a casting process in which molten steel with an adjusted composition is cast to form a steel slab, a hot rolling process in which the steel slab is hot rolled to obtain a hot rolled steel sheet, a coiling process in which the hot rolled steel sheet is coiled, a cold rolling process in which the coiled hot rolled steel sheet is cold rolled to obtain a cold rolled steel sheet, a pickling process in which the cold rolled steel sheet is pickled, a pretreatment process in which the pickled cold rolled steel sheet is brush ground, and an annealing process in which the pretreated cold rolled steel sheet is annealed. Alternatively, the cold rolling process may be carried out directly after pickling without coiling after the hot rolling process.

[0070] [Casting process] The conditions for the casting process are not particularly limited. For example, after melting in a blast furnace or an electric furnace, various secondary smelting processes may be carried out, and then casting may be carried out by a method such as ordinary continuous casting or casting by an ingot method.

[0071] [Hot rolling process] The cast steel slab as described above can be hot-rolled to obtain a hot-rolled steel sheet. The hot rolling step is performed by hot-rolling the cast steel slab directly or after cooling it once and then reheating it. When reheating is performed, the heating temperature of the steel slab may be, for example, 1100°C to 1250°C. In the hot rolling step, rough rolling and finish rolling are usually performed. The temperature and reduction of each rolling step may be appropriately changed depending on the desired metal structure and plate thickness. For example, the finishing temperature of the finish rolling may be 900 to 1050°C, and the reduction of the finish rolling may be 10 to 50%.

[0072] [Winding process] The hot-rolled steel sheet can be coiled at a predetermined temperature. The coiling temperature may be appropriately changed depending on the desired metal structure, etc., and may be, for example, 500 to 800°C. The hot-rolled steel sheet may be recoiled before or after coiling and subjected to a predetermined heat treatment. Alternatively, the coiling step may be omitted, and the hot-rolled steel sheet may be pickled after the hot-rolling step and then subjected to the cold-rolling step described below.

[0073] [Cold rolling process] After the hot-rolled steel sheet is subjected to pickling or the like, the hot-rolled steel sheet is cold-rolled to obtain a cold-rolled steel sheet. The rolling reduction in the cold rolling may be appropriately changed depending on the desired metal structure and sheet thickness, and may be, for example, 20 to 80%. After the cold rolling process, the steel sheet may be cooled to room temperature, for example, by air cooling.

[0074] [Pretreatment process] In order to obtain a fine ferrite phase and its internal oxides in the surface layer of the finally obtained steel sheet, it is effective to carry out a predetermined pretreatment process before annealing the cold-rolled steel sheet. The pretreatment process makes it possible to more effectively introduce strain into the steel sheet, and the strain promotes dislocation of the metal structure of the steel sheet, which makes it easier for oxygen to penetrate into the steel along the dislocations during annealing, making it easier to generate oxides inside the steel sheet. As a result, this is advantageous for increasing the number density of the internal oxides of the ferrite phase. In addition, the internal oxides function as pinning particles and contribute to the refinement of the ferrite phase. Therefore, when such a pretreatment process is carried out, the desired fine ferrite phase and its internal oxides are more likely to be generated in the annealing process described later. The pretreatment process includes grinding the surface of the cold-rolled steel sheet with a heavy-duty grinding brush (brush grinding process). As the heavy-duty grinding brush, D-100 manufactured by Hotani Co., Ltd. may be used. When grinding, it is recommended to apply a 1.0 to 5.0% NaOH aqueous solution to the surface of the steel sheet. The brush reduction amount is preferably 0.5 to 10.0 mm, and the rotation speed is preferably 100 to 1000 rpm. By performing the brush grinding treatment under such coating liquid conditions, brush reduction amount, and rotation speed, a fine ferrite phase and its internal oxides can be efficiently formed in the vicinity of the surface layer of the steel sheet in the annealing step described later.

[0075] [Annealing process] The cold-rolled steel sheet that has been subjected to the above pretreatment process is then annealed. The annealing is preferably performed under tension of, for example, 0.1 to 20 MPa. Applying tension during annealing makes it possible to more effectively introduce strain into the steel sheet, which in turn promotes dislocations in the metal structure of the steel sheet, making it easier for oxygen to penetrate into the steel along the dislocations, and thus facilitating the generation of oxides inside the steel sheet. As a result, this is advantageous for increasing the number density of oxides inside the fine ferrite phase.

[0076] From the viewpoint of generating a fine ferrite phase and its internal oxide, the holding temperature in the annealing step is preferably 700°C to 900°C. If the holding temperature in the annealing step is less than 700°C, the internal oxide may not be generated in a sufficient amount. In addition, the pinning effect of the ferrite phase grain boundary by the internal oxide may be insufficient, and the ferrite phase may become coarse. Therefore, the LME resistance may be insufficient. On the other hand, if the holding temperature in the annealing step is more than 900°C, the internal oxide may become coarse, and the desired internal oxide may not be generated. In addition, if the temperature is more than 900°C, even if the internal oxide is formed, the ferrite phase may grow rapidly and the desired fine ferrite phase may not be obtained. Therefore, the LME resistance may be insufficient. The heating rate to the above holding temperature is not particularly limited, but may be 1 to 10°C / sec. In addition, the heating may be performed in two stages, with a first heating rate of 1 to 10°C / sec and a second heating rate of 1 to 10°C / sec different from the first heating rate.

[0077] The holding time at the holding temperature in the annealing step is preferably 0 to 300 seconds, and more preferably 50 to 130 seconds. Holding time of 0 seconds means that the temperature rise process is heat treated at a predetermined dew point, and immediately after reaching the predetermined temperature, the temperature is cooled without isothermal holding. Even if the holding time is 0 seconds, internal oxides are generated during the temperature rise process, and LME resistance can be obtained. On the other hand, if the holding time is more than 300 seconds, the internal oxides may become coarse and may not be generated in a sufficient amount. In addition, the pinning effect of the internal oxides on the ferrite phase grain boundaries may be insufficient, and the ferrite phase may become coarse. Therefore, the LME resistance may be insufficient.

[0078] During the temperature rise and holding (isothermal) of the annealing process, humidification is performed from the viewpoint of generating fine ferrite phases and their internal oxides. Humidification is started from at least 300°C during the temperature rise. At 300°C or higher, dislocations in the ferrite phase in the steel sheet act as oxygen diffusion paths, and the generation of internal oxides in the ferrite phase by oxygen contained in the humidified atmosphere is promoted. In general, humidification during the temperature rise from about 300°C to the holding temperature promotes the formation of an external oxide film and reduces platability, so those skilled in the art avoid humidification during such a temperature rise process. In addition, when the temperature at which humidification is started exceeds 300°C, particularly at a temperature close to the holding temperature, for example, a temperature of about 700°C, the dislocations in the ferrite phase are restored and disappeared, so that internal oxides in the ferrite phase are not sufficiently generated.

[0079] The atmosphere for humidification has a dew point of more than 10° C. and not more than 20° C., preferably 11 to 20° C., and a hydrogen concentration of 8 to 20 vol% H2, preferably 10 vol% H2. The dew point before humidification is −40 to −60° C., and water vapor is added from there to control the dew point to a predetermined value. If the dew point is too low, the internal oxide layer may not be formed sufficiently. Also, the pinning effect of the internal oxide on the ferrite grain boundaries may be insufficient, causing the ferrite phase to coarsen. As a result, the LME resistance may be insufficient. On the other hand, if the dew point is too high, an outer oxide layer may be formed on the surface of the steel sheet, making it difficult to obtain a plating layer. Even if the dew point is within the above range, if the hydrogen concentration is too low, the oxygen potential becomes excessive, and an outer oxide layer is formed, making it impossible to obtain a plating layer, or an inner oxide layer is not formed sufficiently. As a result, LME resistance may be insufficient. On the other hand, if the hydrogen concentration is too high, the oxygen potential becomes insufficient, and the inner oxide layer is not formed sufficiently, and an outer oxide layer is formed, which may result in a failure to obtain a plating layer. Also, if a sufficient amount of inner oxide is not generated, the pinning effect of the inner oxide on the ferrite phase grain boundary becomes insufficient, and the ferrite phase may become coarse. As a result, the LME resistance may be insufficient.

[0080] Furthermore, when performing the annealing process, it is effective to remove the internal oxide layer of the steel sheet, particularly before the brush grinding process. An internal oxide layer may be formed on the surface layer of the steel sheet during the above-mentioned rolling process, particularly the hot rolling process. Such an internal oxide layer formed in the rolling process may hinder the formation of internal oxides in the annealing process, and may also cause the pinning effect of the ferrite phase grain boundary by the internal oxide to be insufficient, resulting in coarsening of the ferrite phase. Therefore, it is preferable to remove the internal oxide layer before annealing by pickling or the like. More specifically, the depth of the internal oxide layer of the cold-rolled steel sheet when performing the annealing process is set to 0.5 μm or less, preferably 0.3 μm or less, more preferably 0.2 μm or less, and even more preferably 0.1 μm or less.

[0081] By carrying out each of the above-mentioned steps, a steel sheet having a fine ferrite phase and its internal oxides formed in the surface layer of the steel sheet can be obtained.

[0082] <Method of manufacturing plated steel sheets> A preferred method for producing the plated steel sheet according to the present invention will be described below. The following description is intended to exemplify a characteristic method for producing the plated steel sheet according to the present invention, but is not intended to limit the plated steel sheet to one produced by the production method described below.

[0083] The plated steel sheet according to the present invention can be obtained by carrying out a plating treatment step of forming a plating layer containing Zn on the steel sheet produced as described above.

[0084] [Plating process] The plating process may be carried out according to a method known to those skilled in the art. The plating process may be carried out, for example, by hot-dip plating or by electroplating. Preferably, the plating process is carried out by hot-dip plating. The conditions of the plating process may be appropriately set in consideration of the component composition, thickness, and coating weight of the desired plating layer. After the plating process, an alloying process may be carried out. Typically, the conditions of the plating process may be set so as to form a plating layer containing Al: 0-60.0%, Mg: 0-15.0%, Fe: 0-15%, Ni: 0-20%, and Si: 0-3%, with the balance being Zn and impurities. More specifically, the conditions of the plating process may be appropriately set to form, for example, Zn-0.2%Al (GI), Zn-0.8%Al, Zn-4.5%Al, Zn-0.09%Al-10%Fe (GA), Zn-1.5%Al-1.5%Mg, or Zn-11%Al-3%Mg-0.2%Si, Zn-11%Ni, or Zn-15%Mg. From the viewpoint of improving LME resistance, the Al content in the plating layer is preferably 0.3 to 1.5%. EXAMPLES

[0085] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples in any way.

[0086] For the examples and comparative examples of plated steel sheets, samples were prepared according to the following procedure unless otherwise specified. Specific conditions used in some comparative examples will be explained separately. (Preparation of Steel Sheet Samples) Molten steel with adjusted composition was cast to form a steel billet, which was hot rolled, pickled, and then cold rolled to obtain a cold-rolled steel sheet. The cold-rolled steel sheet was then air-cooled to room temperature, and pickled to remove the internal oxide layer formed by rolling to the depth (μm) of the internal oxide layer before annealing shown in Table 1. Samples were then taken from each cold-rolled steel sheet according to a method conforming to JIS G0417:1999, and the composition of the steel sheet was analyzed by ICP-MS or the like. The measured composition of the steel sheet is shown in Table 1. The thickness of all the steel sheets used was 1.6 mm.

[0087] Next, a 2.0% aqueous solution of NaOH was applied to some of the cold-rolled steel sheets, and the sheets were pretreated by brush grinding with a heavy-duty grinding brush (D-100 manufactured by Hotani Co., Ltd.) at a brush reduction of 2.0 mm and a rotation speed of 600 rpm. Thereafter, the sheets were annealed at the hydrogen concentration, dew point, holding temperature and holding time shown in Tables 1 and 2 to prepare each steel sheet sample. The presence or absence of pretreatment and the conditions of the annealing treatment (humidification zone, hydrogen concentration (%), dew point (°C), holding temperature (°C), and holding time (seconds)) are shown in Tables 1 and 2. "Temperature increase" in the column of the humidification zone means that the sheet is humidified in an atmosphere with the aforementioned hydrogen concentration and dew point during the period from 300°C or higher to the holding temperature, and "isothermal" in the column of the humidification zone means that the sheet is humidified in an atmosphere with the aforementioned hydrogen concentration and dew point during the holding time. The temperature increase rate during annealing was 1 to 10°C / second. In the above annealing treatment, the cold-rolled steel sheets were subjected to a tension of 0.1 to 20 MPa or more in the rolling direction. For each steel sheet sample, a JIS No. 5 tensile test piece was taken with the longitudinal direction perpendicular to the rolling direction, and a tensile test was performed in accordance with JIS Z 2241 (2011). As a result, the tensile strength of No. 1 was less than 440 MPa, and the others were 440 MPa or more.

[0088] (Preparation of plated steel sheet samples) After each steel sheet sample was cut to a size of 100 mm × 200 mm, a plating process was performed to form the plating types shown in Tables 1 and 2, to prepare plated steel sheet samples. In Tables 1 and 2, plating type a means "galvannealed steel sheet (GA)", plating type b means "hot-dip Zn-0.2% Al plated steel sheet (GI)", plating type c means "hot-dip Zn-(0.3 to 1.5)% Al plated steel sheet (Al content is shown in Tables 1 and 2)", and plating type d means "electrolytic Zn plating (Al composition less than 0.01%)". In the hot-dip galvanizing process, the cut samples were immersed in a hot-dip galvanizing bath at 440 °C for 3 seconds. After immersion, the samples were pulled out at 100 mm / s, and the coating weight was reduced to 50 g / m by N2 wiping gas. 2 For plating type a, alloying treatment was then carried out at 500°C.

[0089] The obtained plated steel sheet samples were evaluated for each evaluation item using the following evaluation methods. As in Example 1, the tensile strength of No. 1 was less than 440 MPa, and the others were 440 MPa or more. Regarding LME resistance, when the Al content of plating type c was 0.3 to 1.5 mass%, LME resistance was improved. The results are shown in Table 2.

[0090] (Analysis of the surface layer of steel plate samples: Number density of fine ferrite phases) Each steel sheet sample prepared as described above was cut into 25 mm x 15 mm, the cut samples were embedded in resin and mirror polished, and the cross section of each steel sheet sample was observed by SEM. From the cross-sectional SEM image, a test piece for TEM observation was taken using FIB processing so as to include the interface between the plating layer and the steel sheet. In the TEM observation, the ferrite phase corresponding to the shape shown in the present application was identified within a range of 2 μm deep from the steel sheet surface (interface between the plating layer and the steel sheet) to the steel sheet side, and its number density was measured. The observation position was set to 2.0 μm from the steel sheet surface in the depth direction (direction perpendicular to the steel sheet surface), and 1.0 μm from any position in the above TEM image in the width direction (direction parallel to the steel sheet surface). The TEM image of each region of each steel plate sample was binarized, the area of ​​the ferrite phase was calculated from the binarized image, and the circle-equivalent diameter (nm) of the ferrite phase was calculated as the diameter of a circle having the same area as the area thus calculated, i.e., the circle-equivalent diameter. Ferrite phases within the circle-equivalent diameter range of 1 μm or less were defined as fine ferrite phases. Furthermore, the number of fine ferrite phases in the TEM image was counted. The average number of fine ferrite phases in the binarized images at 10 locations thus obtained was defined as the number density of the fine ferrite phases. The number density (pieces / μm) of the fine ferrite phases for each steel plate sample was calculated. 2 ) are shown in Tables 1 and 2.

[0091] (Analysis of the surface layer of steel plate samples: Number density of internal oxides) Each steel sheet sample prepared as described above was cut into 25 mm x 15 mm, the cut samples were embedded in resin and mirror polished, and the cross section of each steel sheet sample was observed by SEM. A test piece for TEM observation was taken from the cross-sectional SEM image by FIB processing so as to include the interface between the plating layer and the steel sheet. In the TEM observation, the internal oxides of the ferrite phase corresponding to the shape shown in the present application were identified within a range of 2 μm deep from the steel sheet surface (interface between the plating layer and the steel sheet) to the steel sheet side, and their number density was measured. The observation position was set to 2.0 μm from the steel sheet surface in the depth direction (direction perpendicular to the steel sheet surface), and 1.0 μm from any position in the above TEM image in the width direction (direction parallel to the steel sheet surface). The TEM image of each region of each steel sheet sample was binarized, the area of ​​the internal oxide was calculated from the binarized image, and the particle size (nm) of the internal oxide was calculated as the diameter of a circle having the same area as the area calculated, i.e., the circle equivalent diameter. Those within the particle size range of 2 to 100 nm were defined as internal oxides. Furthermore, the number of internal oxides in the TEM image was counted. The average number of internal oxides in the binarized images at 10 locations thus obtained was defined as the number density of fine internal oxides. The number density (pieces / μm) of the internal oxides in the ferrite phase for each steel sheet sample was calculated. 2 ) are shown in Tables 1 and 2. In addition, the aspect ratio and minor axis of the internal oxides were also measured, and the number density (pieces / μm) of internal oxides with a given aspect ratio and minor axis was calculated. 2 ) are also shown in Tables 1 and 2. In addition, elemental concentration of the internal oxides was measured by EDS (Energy Dispersed Spectroscopy) to determine the number density (pieces / μm2) of internal oxides with an Al concentration of 20 mass% or more. 2 ) are also shown in Tables 1 and 2.

[0092] (LME resistance evaluation) Each 100 x 100 mm plated steel sheet sample was subjected to spot welding. Two pieces were cut to a size of 50 mm x 100 mm, and the two Zn-based plated steel sheet samples were spot-welded using a dome radius type welding electrode with a tip diameter of 8 mm at an impact angle of 5°, pressure of 4.0 kN, current flow time of 0.5 seconds, and current flow current of 9 kA to obtain welded parts. The cross-sections of the welds were polished and then observed with an optical microscope, and the length of the LME cracks that occurred on the cross-sections of the welds was measured and evaluated as follows. The results are shown in Tables 1 and 2. The plating types in Tables 1 and 2 were as shown in each table. Rating AAA: No LME cracks Rating AA: LME crack length 0μm to 100μm Rating A: LME crack length over 100μm to 500μm Rating B: LME crack length over 500 μm

[0093] [Table 1]

[0094] [Table 2]

[0095] For samples No. 1 to 21, 37 to 40, and 51 to 53 in Table 1, the composition of the steel sheet, the number density of the fine ferrite phase and its internal oxides met the range of the present invention, and therefore the steel sheet had high strength and LME resistance. Samples No. 22 to 36 and 41 to 47 in Table 2 are comparative examples outside the range of the present invention. Sample No. 22 had an insufficient amount of C, and therefore sufficient strength could not be obtained. Sample No. 23 had a low dew point during annealing, and therefore an internal oxide layer was not sufficiently formed, and a fine ferrite phase was not sufficiently formed, and therefore high LME resistance could not be obtained. Sample No. 24 had a high dew point during annealing, and therefore an external oxide layer was formed on the surface of the steel sheet, and therefore a coating layer could not be obtained. Sample No. 25 had a high holding temperature during annealing, and therefore the internal oxides became coarse, and the desired internal oxides could not be obtained, and the ferrite phase also grew, and therefore the desired fine ferrite phase could not be obtained, and therefore high LME resistance could not be obtained. In sample No. 26, the holding temperature during annealing was low, so that the internal oxide was not sufficiently formed, and the pinning effect of the internal oxide on the ferrite grain boundary was insufficient, so that the ferrite phase became coarse, and high LME resistance was not obtained. In sample No. 27, the brush grinding treatment before annealing was not performed, so that the internal oxide was not sufficiently formed, and fine ferrite phase was not formed, and high LME resistance was not obtained. In sample No. 28, the holding time during annealing was long, so that the internal oxide was coarsened, and a sufficient amount of internal oxide was not generated. In addition, the pinning effect of the internal oxide on the ferrite grain boundary was insufficient, and the desired ferrite phase was not formed. Therefore, high LME resistance was not obtained. In samples No. 29 and 31, the Si content and Mn content were excessive, respectively, so that an outer oxide layer was formed on the surface of the steel sheet, and a plating layer was not obtained. In samples No. 30 and 32, the Si content and Mn content were insufficient, so that fine ferrite phase was not sufficiently formed, and high LME resistance was not obtained. Sample No. 33 contained too much Al, so an outer oxide layer formed on the surface of the steel sheet, and no plating layer was obtained. Sample No. 34 contained too little Al, so an inner oxide was not sufficiently formed, and high LME resistance was not obtained. Sample No. 35 did not undergo brush grinding before annealing, so an inner oxide was not sufficiently formed and a fine ferrite phase was not formed, and high LME resistance was not obtained.For sample No. 36, 4 vol% H2 was used as the humidified atmosphere during annealing at a dew point of 20°C, and an outer oxide layer was formed on the surface of the steel sheet, and no plating layer was obtained. For sample No. 41, the cold-rolled steel sheet was not pickled, and the internal oxide layer formed by rolling was left, and then brush grinding and heat treatment were performed under the conditions shown in Table 1. Since the depth of the internal oxide layer of the cold-rolled steel sheet was 0.7 μm, fine ferrite phases and their internal oxides were not sufficiently formed, and high LME resistance was not obtained. For sample No. 42, the holding time during annealing was long, and the internal oxides were coarsened, and a sufficient amount of internal oxide was not generated. In addition, the pinning effect of the internal oxide on the ferrite phase grain boundary was insufficient, and the desired ferrite phase was not formed. Therefore, high LME resistance was not obtained. For sample No. 43, the dew point during annealing was low (in other words, not over 10°C), and a sufficient internal oxide layer was not formed, and high LME resistance was not obtained. In the case of No. 44, the dew point during annealing was high, and an outer oxide layer was formed on the surface of the steel sheet, and no coating layer was obtained. In the case of sample No. 45, a humidified atmosphere with a dew point of 11°C and 7 vol% H2 was used during annealing, and an outer oxide layer was formed, but an inner oxide layer was not sufficiently formed, resulting in insufficient LME resistance. In the case of sample No. 46, a humidified atmosphere with a dew point of 11°C and 22 vol% H2 was used during annealing, and an inner oxide layer was not sufficiently formed, resulting in insufficient pinning effect of the inner oxide on the ferrite phase grain boundary, resulting in coarsening of the ferrite phase, and insufficient LME resistance. In the case of sample No. 47, humidification was not performed during heating, but only during isothermal heating, and therefore a sufficient amount of inner oxide was not generated. As a result, high LME resistance was not obtained.

[0096] In the inventive examples, fine ferrite phases and their internal oxides were confirmed near the steel sheet surface. Therefore, high LME resistance was obtained. On the other hand, in the comparative examples, fine ferrite phases and their internal oxides were not properly formed near the steel sheet surface. Therefore, at least one of the following was confirmed: poor LME resistance or no coating layer was obtained. [Industrial Applicability]

[0097] According to the present invention, it is possible to provide a high-strength plated steel sheet having high LME resistance, and the plated steel sheet can be suitably used for applications such as automobiles, home appliances, and building materials, particularly for automobiles, and is expected to have high collision safety and long life as an automobile steel sheet and an automobile plated steel sheet. Therefore, the present invention can be said to be an invention of extremely high industrial value.

Claims

1. A plated steel sheet having a plating layer containing Zn on a steel sheet, the steel sheet having a tensile strength of 780 MPa or more and a chemical composition of the steel sheet, in mass%, C: 0.05-0.40%, Si: 0.2-3.0%, Mn: 0.1 to 5.0%, sol. Al: 0.4 to 1.50%, P: 0.0300% or less, S: 0.0300% or less, N: 0.0100% or less, B: 0 to 0.010%, Ti: 0 to 0.150%, Nb: 0 to 0.150%, V: 0 to 0.150%, Cr: 0-2.00%, Ni: 0-2.00%, Cu: 0-2.00%, Mo: 0-1.00%, W: 0-1.00%, Ca: 0-0.100%, Mg: 0-0.100%, Zr: 0 to 0.100%, Hf: 0 to 0.100%, and REM: 0 to 0.100%, with the balance being Fe and impurities; In any vertical cross section of the steel plate, in a region from the surface to a depth of 2 μm, ferrite phases having a circle equivalent diameter of 1 μm or less are present at a number density of 2 to 30 particles / μm 2 The ferrite phase contains internal oxides with a circle equivalent diameter of 2 to 100 nm at a number density of 3 particles / μm 2 Plated steel sheet containing the above.

2. The shape of the inner oxide has an aspect ratio of 1.5 to 20, a minor axis of 1 to 20 nm, and a number density of 3 to 30 particles / μm 2 The plated steel sheet according to claim 1 ,

3. 3. The plated steel sheet according to claim 1, wherein the inner oxide is one or more of Al and O, Al, Si and O, Al, Mn and O, or Al, Si, Mn and O, and the Al contained in the inner oxide is 20 to 53 mass %.

4. The plated steel sheet according to claim 1 or 2, wherein the plating layer has a component composition containing, in mass%, 0.3 to 1.5% Al, with the balance being Zn and impurities.

5. The plated steel sheet according to claim 1 or 2, wherein the plating layer has a component composition containing, in mass%, Al: 0 to less than 0.1%, with the balance being Zn and impurities.

Citation Information

Patent Citations

  • High-strength plated steel sheet, as well as method for producing the same

    JP2016130357A

  • High strength plating steel sheet excellent in plating property, processability and delayed fracture resistance, and manufacturing method therefor

    JP2018193614A

  • Spot welding member

    JP2020179413A

  • Galvanized steel sheet with high resistance spot weldability

    JP2020524743A

  • Alloyed hot-dip galvanized steel plate and manufacturing method therefor

    WO2014102901A1